Notarical Ethics In The Implementation Of Murabaha - Ebit Tri Laksono; Akhmad Khisni (Jurnal Akta, 2018)
In a business and banking transactions, there is an important thing of the existence of agreement, especially in a debt-receivable case. A Public notary as the side that has a discretionary power in making authentic agreement which has an important role in the banking transaction, not only in the Conventional Bank but also in the Islamic Bank. On of them is in the making of sharia agreement by the principal of murabaha. The agreement that was made by the public notary had the obvious strong power and could be placed as the evidence instrument, if there is a problem between two parties. The making of an authentic agreement by the public notary was required in the legislative regulations with the aim to create certainty, public order and the protection of the law.Keywords: Public Notary; Sharia; Murabaha.